Regional Differences in Susceptibility to Hypoxic-Ischemic Injury in the Preterm Brain: Exploring the Spectrum from White Matter Loss to Selective Grey Matter Injury in a Rat Model - D. B. Selip; L. L. Jantzie; M. Chang; M. C. Jackson; E. C. Fitzgerald; G. Boll; A. Murphy; F. E. Jensen (Neurology Research International)
Models of premature brain injury have largely focused on the white matter injury thought to underlie periventricular leukomalacia (PVL). However, with increased survival of very low birth weight infants, injury patterns involving grey matter are now recognized. We aimed to determine how grey matter lesions relate to hypoxic-ischemic- (HI) mediated white matter injury by modifying our rat model of PVL. Following HI, microglial infiltration, astrocytosis, and neuronal and axonal degeneration increased in a region-specific manner dependent on the severity of myelin loss in pericallosal white matter. The spectrum of injury ranged from mild, where diffuse white matter abnormalities were dominant and were associated with mild axonal injury and local microglial activation, to severe HI injury characterized by focal MBP loss, widespread neuronal degeneration, axonal damage, and gliosis throughout the neocortex, caudate putamen, and thalamus. In sum, selective regional white matter loss occurs in the preterm rat concomitantly with a clinically relevant spectrum of grey matter injury. These data demonstrate an interspecies similarity of brain injury patterns and further substantiates the reliable use of this model for the study of preterm brain injury.